Placental expression of estrogen and progesterone receptors and vascular endothelial growth factor in buffaloes suffering from uterine torsion - Yahia A. Amin; Ahmed Abdou Elnegiry; Eatemad A. Awadalla; Hassan A. Hussein; Ragab H. Mohamed (BMC Veterinary Research)
Abstract Background Although several risk factors have been suggested for uterine torsion, the pathogenesis is still unclear. Therefore, the current study aims to investigate the pathogenesis of uterine torsion by assessing the histological, histochemical, and immunohistochemical changes that occur in the placenta obtained from uterine torsion cases. Immunohistochemical changes include investigation of the expression of estrogen receptors (ERs), progesterone receptors (PRs), and the vascular endothelial growth factor (VEGF) in the placental tissue. Methods Forty intrapartum dairy cows were included in this investigation. The cows were divided into two equal groups. The first group was the uterine torsion (UT) group, while the second group was the normal control group (Ctrl). After caesarian section treatment, placentas were collected from all animals in the study. Histopathological, histochemical, and immunohistochemical examinations were performed. Estrogen receptors, progesterone receptors, and vascular endothelial growth factor expression in the placenta were evaluated. Results The results revealed numerous trophoblast giant or binucleate cells in the trophoblastic epithelium. Through Masson’s trichrome technique, the distribution of collagen fibers as shiny, blue-colored stripes on the fetal mesenchyme was observed. Additionally, the results showed a strong, intense PAS-positive reaction in the cytoplasmic vesicles of most trophoblastic cells due to mucopolysaccharides. The immunohistochemical findings of the UT placenta revealed moderate to weak staining for ERs in contrast to those of the Ctrl placenta, which revealed moderate staining for ERs. In addition, non-statistical differences in the expression of PRs were found between the two tested groups. For VEGF, strong positive immunoreactivity was found in the Ctrl group compared to the UT group, which exhibits a general absence in many trophoblast cells. Conclusion It can be concluded that significant variation was observed in the placentas obtained from buffaloes suffering from UT compared to those obtained from normal pregnant ones. These significant variations were involved in the decreased expression of ERs and VEGF in the UT group compared to the normal Ctrl one. Investigating the expression of these placental molecules may monitor the changes in the placental tissue and provide insight into the pathogenesis of UT.